Differential motor alterations in children with three types of attention deficit hyperactivity disorder - Adrián Poblano; Belinda Luna; César Reynoso (Arquivos de Neuro-Psiquiatria)
Objective To determine frequency of motor alterations in children with attention deficit hyperactivity disorder (ADHD). Method We evaluated 19 children aged 7-12 years with ADHD classified in three sub-types: Combined (ADHD-C), with Inattention (ADHD-I), and with Hyperactivity (ADHD-H). Controls were age- and gender matched healthy children. We utilized Bruininks-Oseretsky Test of Motor Proficiency (BOTMP) for measuring motor skills. Results We observed differences between children with ADHD and controls in BOTMP general score and in static coordination, dynamic general- and hand- coordination, and in synkinetic movements. We also found differences in dynamic hand coordination between controls and children with ADHD-C; in dynamic general coordination between controls and children with ADHD-H; and in frequency of synkinetic movements between controls and children with ADHD-H. Conclusion Children with ADHD with a major degree of hyperactivity showed greater frequency of motor alterations.